2001
DOI: 10.1097/00000539-200112000-00056
|View full text |Cite
|
Sign up to set email alerts
|

A Dose Response Study of Clonidine with Local Anesthetic Mixture for Peribulbar Block: A Comparison of Three Doses

Abstract: We studied the effect of the addition of 0.5, 1.0 and 1.5 microg/kg clonidine to a lidocaine-hyaluronidase mixture on the onset and duration of peribulbar block and perioperative analgesia. A dose of 1.0 microg/kg produced a significant increase in duration of anesthesia and analgesia with minimal side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 10 publications
2
35
0
Order By: Relevance
“…At a dose of 100-150 μg, clonidine resulted in a reduction in intraoperative stress associated with surgery and a decrease in IOP [17]. There are few studies using clonidine in ophthalmic blocks, most of them combining clonidine with local anesthetics for peribulbar blocks in cataract surgery [12][13][14]. Cataract surgery is recognized as a procedure associated with minimal pain; phacoemulsification is even performed with topical anesthesia [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At a dose of 100-150 μg, clonidine resulted in a reduction in intraoperative stress associated with surgery and a decrease in IOP [17]. There are few studies using clonidine in ophthalmic blocks, most of them combining clonidine with local anesthetics for peribulbar blocks in cataract surgery [12][13][14]. Cataract surgery is recognized as a procedure associated with minimal pain; phacoemulsification is even performed with topical anesthesia [18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies that used clonidine in ophthalmic blocks have reported contradictory results [11][12][13][14]22]. In a dose-response study of 2% lidocaine peribulbar block for cataract surgery, Madan et al found a dose-dependent prolongation of anesthesia and analgesia [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] Clonidine has also been used to treat and/or prevent diarrhea, 25 manic and bipolar symptoms, 26 muscle rigidity and spasticity, 27 hyperactivity and attention deficit disorder in children, 28 withdrawal states, 29-32 congestive heart failure, 33 new-onset rapid atrial fibrillation, 34 angina pectoris, 35 myocardial infarction, 36 post-general anesthesia shivering 37 and agitation, 38-41 glaucoma, 42 chronic pain, 43 and syncope. 44 It can also supplement peribulbar, 45 epidural, 46 and intrathecal anesthesia. 47 Recently, clonidine has been utilized as a preoperative medication providing anxiolysis, 12,48 sedation, 49 analgesia, 11,50,51 hemodynamic stability, 13,50-53 saliva control, 23,54 and antiemetic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Opioids, clonidine, ketamine and prostigmine have been added to local anaesthetics and injected extradurally, intrathecally or in nerve plexuses for a more intense and prolonged analgesia 3,4,5,6,7,8 . Opioids are commonly added to local anaesthetic solutions to increase intensity and duration of anaesthesia by acting on opioid receptors present on the nerve terminals 9,10 . However, fentanyl has some side effects as vomiting and respiratory depression 7 .…”
Section: Introductionmentioning
confidence: 99%